Laparoscopic transabdominal cervical cerclage by broad ligament window technique - B Ramesh; T M Chaithra; G Prasanna (Wolters Kluwer Medknow Publications, 2018)
Laparoscopic transabdominal cerclage (LTAC) is a well documented procedure for cervical incompetence. In this article we have done a detailed stepwise description of LTAC by broadligament window technique. This technique makes the procedure simpler, safer and easy to reproduce.